(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2026)
This study aims to analyze the impact of audit quality on reducing financial fraud within selected economic institutions in Western Algeria. To achieve this objective, a questionnaire was employed as the primary data collection tool, with a final sample of 78 respondents comprising executives, accountants, and internal and external auditors working in these institutions. Data analysis was conducted using SPSS version 26, and the results revealed a statistically significant effect of audit quality on mitigating financial fraud in the studied institutions, although the role of external audit was found to be limited. Based on these findings, the study recommends enhancing and activating communication channels between audit committees and both internal and external audits to ensure effective information sharing and better coordination in combating and reducing fraudulent practices.